The role of female executives on corporate governance conformity: a cross-sectional analysis in an emergent market - Dănescu, Tatiana; Popa, Maria-Alexandra (Journal of Business Economics and Management, 2022)
Previous studies have shown the importance of gender diversity for good corporate governance, although in developing countries a gap is observed in correlating compliance with corporate governance principles and board composition. Our study examines the influence of the board composition, including female executives, on compliance with the corporate governance code of companies listed on the Bucharest Stock Exchange. By analysing data collected from the annual reports (corporate governance statements, financial statements) of 63 companies listed on the Romanian capital market between 2016 and 2019 (divided into two panels depending on the listing tier – Premium and Standard), we identified a positive relationship between female executive and the degree of compliance with the Corporate Governance Code. The national majority capital positively and significantly influences the compliance of companies with female executives listed in the Standard Tier with the Code, while the private majority capital negatively influences the compliance of the companies regardless the listing tier. Our study highlights the importance of female executives in the corporate governance of listed companies on the Romanian capital market and brings empirical contribution to the literature development on a newly declared emerging market.First published online 06 September 2022